Truths and myths about marketed anti-aging skin products: a systematic review - Barnawi, Ghassan M.; Barnawi, Azhar M. (International Journal of Research in Medical Sciences, 2021)
Aging of the skin naturally occurs with increasing age due to several factors involving the reduction of collagen, elastin and many other proteins which help maintain strength and integrity of the skin. Several strategies and treatments were developed to fight and slow down this unstoppable ongoing natural process, however, many of the widely available products may not be as efficient as advertised. The aim was to discuss and investigate the truths and myths about skin anti-aging products and strategies by reviewing the previous studies conducted on this subject. Google scholar database was explored to search for articles related to the current subjects starting from 2010 till 2021. The included searching terms were a combination of anti-aging strategies and efficacy, anti-aging products and myths, anti-aging products and usage of women and perception and attitude of women and anti-aging strategies. The inclusion criteria included original articles conducted on anti-aging products and strategies and full text articles. A total of 40 articles were obtained, only three articles were eligible for the inclusion criteria. The three studies included a total number of 192 participants. Some anti-aging products were found to improve skin health and improve the level of coarse and fine wrinkles and lines. However, their efficacy was limited and doesn’t act as magic.